An Garda Síochána: Culture, challenges, and change - MARSH, COURTNEY NICOLE (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2020)
An Garda Síochána: Culture, challenges, and change is an exploration and understanding of the organisational culture of An Garda Síochána Ireland's National Policing Organisation. While the Gardaí or officers are often in the news media, there has been very little academic research on who and what this organisation is. On an abstract level, organisational culture provides the framework of the basic rules necessary to function, or survive, in an organisation. Police organisational culture provides an identity to officers that performs this same function. On a more specific scale, internationally, police culture has been understood to consist of masculinity, discrimination, exclusion, suspicion, isolation, solidarity/loyalty, moral and political conservatism, pragmatism, cynicism, aggression, negative views of supervision, selective enforcement of the law, and a prioritisation of the crime fighter role over service oriented role. However, this understanding has been gathered from countries with very different policing organisations to Ireland. While the international research in police organisational culture is quite vast, there is relatively little to fill this area in Ireland, particularly when you exclude historical accounts of Irish policing and Northern Ireland. Of those studies that have been identified, very few specifically look at the organisation s culture. Further to this, many of those studies are limited in numerical and geographic scope. While the relatively narrow field has limited a grounding for the findings of this study, they do provide a starting point for identifying what gap needs to be filled, namely an expansive study on the organisation s culture that is not confined to a small number of Gardaí or one geographic region. This considered, the gap identified in the Irish literature is one facet of this research. Naturally if there if the research in this area is underdeveloped in Ireland, then there is also a missing piece of where Ireland situates itself in the international policing literature. The Garda are a unique policing organisation, as such, this type of police culture has not been studied extensively internationally. One of the aims of this research is to understand where Ireland positions itself in the wider world of police organisational culture literature. However, in order for this to be done, and the primary aim of this research, you first need to gain a deeper understanding of what the culture of the Garda is and how this impacts relations within the organisation as well as their relationship with the communities in which they work. While the area of police organisational culture can be quite abstract, some of the more specific aspects of the culture this research aims to understand are in organisational relationships, accountability, and managing change. Though the aims listed thus far are wholly substantive, there is also remit for connecting these findings to a theoretical basis in social learning, social identity, and rotten apple theories to further understand how the culture of the Garda is transmitted throughout the organisation and over time. While this research fills a theoretical and empirical gap, there is also a methodological innovation in how the data was obtained and analysed. Certainly underutilised in Ireland, document analysis in the area of police organisational culture is also underutilised internationally. The data used in this research was obtained from eight documents, consisting of several thousands of pages of text, and spanning a 30 year period. The data from the documents was thematically analysed and a story was constructed based on the data to provide a deeper understanding of what the Garda culture is. While the documents of course contained the data necessary to provide an understanding of Garda culture, perhaps one of the more advantageous contributions of this methodology is the extended observation period provided that allowed for an analysis of the Garda culture over time, something not typically possible in other data collection methods due to their point in time collection nature. This research has contributed many key findings to the understanding of Garda culture. The first approach was to look at the organisation s culture from a top down level and what the relationship between the organisation and its members is. The findings in this area included what type of policing organisation the Garda is and what resources the organisation provides to its members (these resources included both physical resources as well as services provided). From this discussion stemmed a reconceptualization of the traditional types of policing organisations (i.e. militaristic and community/service oriented) as the Garda does not wholly fit in to either. Beyond this, the resources were examined in relation to making do with what little they are given despite increased demand for their services as well as how Gardaí are then left to cope with the added burdens. In particular reference to mental health provisions, how the organisation facilitated, or rather did not, practical and beneficial mental health services was looked at. Further to this organisational relationship from a top down perspective was an understanding of both internal and external organisational relationships and how these are influenced by the training Gardaí receive. These included how the Gardaí interact with each other on an individual level, encompassed within this is the idea that silence is necessary for survival in the organisation, as well as the Gardaís relationship with and to the communities they work in. In terms of training, as well as in conjunction with the idea of socialisation and Social Learning Theory embedding these characteristics into the organisation s culture and its members, it was found that the Gardaí are separated from the community from the outset of their training. This strengthened the earlier proposed idea that the Garda do not truly fit into a community oriented policing style. Internally, the relationships among Gardaí were examined both in relation to how they reacted to external and internal threats and it was concluded that the Gardaí overwhelmingly value self-preservation over loyalty. Chapter seven looked closer at accountability and blame within the organisation and how the lack of accountability on a wide scale coupled with the ever present blame culture impacts on Gardaí behaviour and actions. Though some of the examples given were seemingly indicative of individual level actions, it was argued that, stemming from Rotten Apple Theory, these behaviours are manifestations of organisational level behaviours that have been observed and learned by individual members and acted out based on this observation. In essence, even when behaviour was observed at an individual level, it was still reflective of organisational culture as rotten apples do not form in isolation but rather stem from rotten orchards. The final chapter brought the findings together with an added theoretical lens and the previous Irish and international literature to more fully understand where the Garda, and Ireland, fit into a larger scope of police organisational culture. It was reflected that while Ireland has always been considered quite different to many other international policing organisations, the more recent literature, particularly from the UK, seems to be more in line with some of the Irish characteristics found in the Garda culture. However, what this means for police culture as a whole, has still not been fully explored.
APPROVED
Keywords: Irish policing; police culture; police organisational culture; An Garda Siochana; document analysis